Cell wall degrading enzyme secretion by Colletotrichum acutatum, the causative fungus of secondary leaf fall of Hevea brasilieneis - Fernando T H P S; Jayasinghe C K; Wijesundera R L C (Mycological Research, 2001)
Colletotrichum acutatum is the major causative agent of secondary leaf fall disease of rubber. All isolates of the fungus examined secreted polygalacturonase (PG), pectin lyase (PL) and the cellulotic enzymes, B-glucosidase, and cellobiase in culture. Molecular weight determinations suggest that PG as well as the PL produced by all isolates are similar. PG activity was absent in infected tissues associated with the enlargement of lesions. B-glucosidase was present in both healthy and infected leaves while cellobiase was detected only in infected leaf tissue.
Source Year: 2002
Keywords: Colletotrichum acutatum; Hevea brasiliensis; Secondary leaf fall